Production and characterization of solid lipid microparticles loaded with guaraná (Paullinia cupana) seed extract. (September 2019) - Silva, Marluci P.; Thomazini, Marcelo; Holkem, Augusto T.; Pinho, Lorena S.; Genovese, Maria I.; Fávaro-Trindade, Carmen S.
Abstract: Guaraná is a native fruit of the Amazon rainforest, which presents high levels of phenolic compounds. However, these bioactive compounds may be unstable in food processing and gastrointestinal conditions. Thus, this work aimed to characterize guaraná seed extract (GSE) followed by microencapsulation using a spray-chilling method and with vegetable fat as carrier, as well as to evaluate the particles. Phenolic-rich GSE was produced using 50% ( w /w) hydroalcoholic solution and dehydrated by spray drying and lyophilization. Powdered GSE was characterized in relation to its inhibitory activity on digestive enzymes. Solid lipid microparticles (SLM) were evaluated for the retention of bioactive compounds and the release profile of phenolic compounds in simulated gastrointestinal conditions. Powdered GSE showed anti-obesity potential due to the high inhibitory activity of lipase. Regarding the retention of phenolic compounds, at least 75% were detected after 90 days at 25 °C in SLM. Moreover, SLM loaded with 7.5% GSE released approximately 99% of phenolic compounds in simulated gastrointestinal conditions. These results show the efficiency of spray chilling for protection and release of phenolic compounds from GSE, allowing future application in food. Graphical abstract: Unlabelled Image Highlights: Encapsulation promoted the controlled release of phenolic compounds on SGC. Retention of phenolic compounds into SLM were above 75% after 90 days at 25 °C. All formulations presented attractive color and free-flowability.